Optimalisasi Wakaf sebagai Instrumen Pembiayaan UMKM untuk Pengembangan Industri Halal : The Optimization of Waqf as a MSME Financing Instrument for the Halal Industry Development - Ade Nur Rohim (Jurnal Bimas Islam, 2021)
Capital is still a major problem faced by MSMEs, especially in this pandemic era. As one of the Islamic financial instruments, waqf can contribute directly to developing MSMEs through financing schemes aimed at the welfare of the people. This article aims to elaborate and explore the optimization of waqf as an alternative financing instrument for MSMEs that is in accordance with sharia and halal principles. From the elaboration of concepts and characteristics possessed, both by UMKM and waqf, it is concluded that endowments and MSMEs have a very close relationship in the effort to realize community welfare. Optimization of waqf as a financing instrument for SMEs is carried out while still referring to the halal business undertaken, as well as contracts (‘aqd) that are in accordance with sharia principles in the distribution of waqf. Thus, the development of waqf optimization through financing schemes and their utilization will have direct implications on the development of the halal industry, which aims to realize the welfare of the community.